Exploiting Unique Structural and Functional Properties of Malarial Glycolytic Enzymes for Antimalarial Drug Development. (16th December 2014) - Alam, Asrar; Neyaz, Md. Kausar; Ikramul Hasan, Syed
Abstract : Metabolic enzymes have been known to carry out a variety of functions besides their normal housekeeping roles known as "moonlighting functions." These functionalities arise from structural changes induced by posttranslational modifications and/or binding of interacting proteins. Glycolysis is the sole source of energy generation for malaria parasite Plasmodium falciparum, hence a potential pathway for therapeutic intervention. Crystal structures of several P. falciparum glycolytic enzymes have been solved, revealing that they exhibit unique structural differences from the respective host enzymes, which could be exploited for their selective targeting. In addition, these enzymes carry out many parasite-specific functions, which could be of potential interest to control parasite development and transmission. This review focuses on the moonlighting functions of P. falciparum glycolytic enzymes and unique structural differences and functional features of the parasite enzymes, which could be exploited for therapeutic and transmission blocking interventions against malaria.